Reflection of the Freedom Movements on the Relationship between Political Power and Architecture in Paris: Architectural Competitions - Sahtiyanci, Elif; Kirci, Nazan (International Journal of Architectural Engineering Technology, 2022)
As its most prominent financier and employer, architecture is closely related to religious, political, and economic power. According to Lefebvre, representation spaces are established to permanently represent politics and ideology and their transmission to new generations. The democratic attitude of the political power will only change the perception known with the representation spaces. Therefore, this study deals with the example of Paris, which was indicated as the capital of the freedom movements initiated in the 1960s, to demonstrate how the relationship between political power and ideology with architecture transformed under the influence of democracy and freedom movements. For this purpose, political ideology between 1960-90 formed in the De Gaulle period and reached the highest level in the Mitterrand time, attracting the entire world's attention, and its relationship with architecture is investigated. Democratic, pluralistic, participatory, and transparent approaches in politics brought architectural competitions to the agenda by seeking transparency, pluralism, and participation in the production method of architecture above all. These architectural competitions were organized for Paris to reflect the ideological perspective. The crucial result of the libertarian perspectives concerning the city is the importance of publicity as a factor containing the shared spaces of people. The important results concerning the field of architecture are the support of the formation of new ideas, the production of buildings that are the leading symbols of new movements, and providing equality of opportunity for architects.